Vaginal lacerations during laparoscopic hysterectomy for endometrial cancer and local recurrence risk - Olivia Nicolais; Mackenzie Cummings; Tommy R Buchanan, Jr; Lea Moukarzel; Nicholas Cardillo; Elizabeth Burton; Mitchell I. Edelson; Mark S. Shahin (Elsevier, 2024)
Objective: Laparoscopic surgery (MIS) offers equivalent oncologic outcomes as compared to open surgery, while causing lesser morbidity and resulting in a faster recovery. Vaginal extraction of specimens may cause vaginal or perineal lacerations (VL). The objective of this retrospective study was to assess local recurrence rates compared between cases with vaginal laceration (VL) or without vaginal lacerations (NL). Methods: We identified patients with endometrial cancer who underwent MIS between 2014 and 2018. We assessed the rate of local recurrence between patients in VL and NL cohorts. The study included all histologic subtypes and stages while benign final pathology, synchronous primaries or cases that required laparotomy for extraction were excluded. Results: 338 MIS cases were evaluable of which 40 cases had a vaginal laceration during specimen extraction. There was no significant difference in age, race, presence of LVSI, stage, grade, histology or use of vaginal brachytherapy between cohorts. Cases with vaginal lacerations were significantly associated with a higher median BMI and larger uterine size. The VL cohort was more likely to have received adjuvant treatment. In early stage disease, more cases had non-endometrioid histology in the VL group and had increased incidence of chemotherapy and radiation use as well. There were no cases of isolated vaginal recurrence (0/40) in the VL group as compared to an incidence of 2 % (7/298) in the NL group with a relative risk of 0.48 (CI: 0.03-8.36, p = 0.62). There were 4 cases of pelvic recurrence (4/40) in the VL group and 2 cases in the NL group (2/298) with a relative risk of 2.13 (CI: 0.46-9.89, p = 0.34). Conclusions: In endometrial cancer cases, we did not observe a significantly increased risk of vaginal or pelvic recurrence after a vaginal laceration at the time of specimen removal.